"Just Over Here Floating Around": Geographically Bound Professionals in Student Affairs. Issue 5 (20th October 2021) - Kodama, Corinne M.; Narui, Mitsu; Walterbusch, Tracey
Abstract : This study examined the phenomenon of being geographically bound as a student affairs professional. Participants described challenges in career advancement, tension between personal and professional aspirations, and self-doubt about their professional identity due to pervasive messaging that "you need to move out to move up." Results have implications for the socialization of student affairs professionals and how privileging the norm of mobility may create a sense of marginalization for those who cannot relocate.